PERILAKU MASYARAKAT DALAM MENGELOLAH SAMPAH RUMAH TANGGA DI KELURAHAN PENFUI KECAMATAN MAULAFA KOTA KUPANG - Sina, Sudirman; Wulakada, Hamza Huri; Sunimbar, Sunimbar (Universitas Nusa Cendana, 2023)
This study aimed to determine community behavior in managing household waste and the factors that influence community behavior in managing household waste in Penfui Village, Maulafa District, Kupang City. The research method used is a qualitative method. The collecting data using questionnaires, observations, interviews, and documentation. The researcher uses a sampling technique with the Slovin technique. The theory used to analyze the data is Coleman's Rational Choice theory. The result of the study shows that the people in Penfui Village in managing household waste prefer to burn it. It is because the Penfui people have large yards to burn their garbage. However, some residents who do not have yards choose to order other people to pick up the trash and burn it elsewhere. There were dumped in the Penfui market area. The researcher also found the people throw them on the side of the road. The people do this because there are no facilities and infrastructures to dispose garbage. Moreover, public knowledge about the type of waste is still lacking. The community do not know about sorting waste based on its type. Then another reason is for health. Some people choose to burn it because it functions as 'confectionary' and 'cutik geni'.